Gen Z' Critical Thinking Skills Empowering Using E-Worksheet with Problem-Based Learning Model on Mutation Material Assisted by Bioinformatics Database - Meli Astriani; Wulandari Saputri; Agustin Dwi Cahayu; Harry Subianto (Postgraduate, University of Mataram, 2024)
Life in the 21st century demands graduates who can think critically, innovate, collaborate, communicate, and face the changes that occur in the global world. The demands of 21st-century learning have implications for complex learning processes, requiring students' critical thinking skills. This research aims to determine the effect of electronic worksheets (e-worksheets) assisted by bioinformatics integrated with the problem-based learning (PBL) learning model to improve students' critical thinking skills at SMA Muhammadiyah Palembang. The type of research that will be used is Research & Development research. This research is the final stage of the 4D development model. The population of this research was Muhammadiyah High Schools 1, 5, and 6 in the city of Palembang (accreditation A), and the research sample included XII students and biology teachers. Research data analysis used the SPPSS program to carry out the Kolmogorov-Smirnov, homogeneity, and Wilcoxon tests. The pretest and posttest scores were calculated using the N-Gain test. The research results showed that the overall analysis data increased students' critical thinking skills in experimental and control classes. The results of the normality test of pretest and posttest critical thinking data from the three schools showed that the data was normally distributed. Differences in data on students' critical thinking skills are also known from the sig value. 0.000 < α 0.05, which can be concluded that students' critical thinking skills are higher before and after being taught compared to classes with conventional learning.